Teachers' use of situated learning approaches to teach environmental topics in Natural Science and Health Education: a multi-case study of two Namibian teachers - Mamili, Joy Z (Rhodes University, Faculty of Education, Department of Education, 2017)
This study focuses on the use of situated learning approaches in the teaching of environmental topics in Natural Science and Health Education (NSHED) and is the first of its kind in Namibia. Although situated learning approaches, as examples of learner-centred pedagogy, are advocated in national education policies, little empirical research has been conducted in Namibia into how situated learning approaches play out in classroom practice. Therefore, the goal of this study was to find out how NSHED teachers use situated learning approaches when teaching environmental topics. The study reviews the characteristics of situated learning theory and clarifies situated learning approaches as a form of learner-centred pedagogy which is actively promoted in the Namibian schooling system. The study commences with a contextual profile of the communities around the two selected schools. This describes the socio-economic and social-ecological context in which learners are taught about environmental topics. The profile also describes the under-performance of the schools in recent national assessments, especially in relation to environmental topics in NSHED. Drawing on data generated through document analysis, semi-structured interviews and classroom observations, the study concluded that: 1. NSHED teachers both knew about and wished to create an authentic context to enhance situated learning approaches. However, their understandings and applications of situated learning tended to be basic. 2. Teachers dominated the scaffolding process and their scaffolding strategies did not enable learners to increase independence in performing. 3. Despite the use of situated learning approaches, learners' engagement with lesson content was superficial, and the teachers did little to encourage deeper reflections or critical thinking. 4. The teachers appeared to use situated learning approaches to clarify subject content but not to encourage broader environmental understanding, action-taking and change. Based on the research findings, the study recommends that situated learning approaches be integrated into pre- and in-service teacher training with the aim of enhancing teachers' understanding regarding the use of situated learning approaches in the teaching of environmental topics in NSHED.
Keywords: Environmental education -- Namibia; Science -- Study and teaching -- Namibia -- Cast studies; Health education -- Namibia -- Case studies